Problems of toxicity of precious stones - Artyukh, Tatiana (My University, 2000)
The paper presents the study jewelry stones in Ukraine for the indicators of strength, hardness, corrosion resistance and safety performance. В статті наведено дослідження ювелірних камней в Україні за показниками міцності, твердості, корозійної стійкості та показниками безпечності.
Keywords: ювелірні вироби; алергія; безпечність; токсичність; фальсифікація якості; jewelry; stones allergenicity; safety; toxicity; falsification of quality; кафедра експертизи харчових продуктів